Validation of Thin-Layer Chromatography-Bioautographic Method for Determination of Streptomycin - Isnaeni Isnaeni; Andri Astuti; Muhammad Yuwono (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2017)
Background: A simple bio-assay for determination of streptomycin hyphenated with planar chromatography techniques was developed. Objective: This study aims to validate the method for identification and determination of streptomycin in injection preparations with TLC-bioautography. Methods: Thin Layer Chromatography (TLC) was performed on the silica Gel GF-254 using KH2PO4 solution as mobile solvent. The visualization was performed by spraying 2% resorcinol. Direct bi autography was developed using Escherichia coli ATCC 25922 as a bacterial test, grown on the nutrient agar medium at 37oC for 24 hours. The method was validated corresponding to linearity, limit of detection (LOD), intra day precision, and accuracy parameters. The accuracy was measured using streptomycin injection as a sample. Results: The Results showed that the KH2PO4 solution at 7.5% concentration was found to be the optimized solvent with Rf value of 0.5. The linear equation was y = 10.176x + 4.046 at 150 - 350 µg/mL concentration range with the linearity coefficient, Limit of Detection, accuracy, and variation coefficient were 0.9907; 40 ppm; 96.37 + 2.22% (with an RSD value of 2.31%); and 1.63 respectively. Conclusion: The prospective TLC-bioautographic method was applied for the identification and determination of streptomycin in a preparation using a single eluent KH2PO4. The eluent system optimization remains necessary for the identification and determination of the mixture of streptomycin with other antibiotics, such as aminoglycoside groups.